A Comparative Study of Amide Proton Transfer Weighted Imaging and Intravoxel Incoherent Motion MRI Techniques Versus (18) F‐FDG PET to Distinguish Solitary Pulmonary Lesions and Their Subtypes. Issue 5 (1st November 2021) - Fang, Ting; Meng, Nan; Feng, Pengyang; Huang, Zhun; Li, Ziqiang; Fu, Fangfang; Yuan, Jianmin; Yang, Yang; Liu, Hui; Roberts, Neil; Wang, Meiyun
Abstract : Background: Amide proton transfer weighted imaging (APTw), intravoxel incoherent motion (IVIM), and positron emission tomography (PET) imaging all have the potential to characterize solitary pulmonary lesions (SPLs). Purpose: To compare APTw and IVIM with PET imaging for distinguishing between benign and malignant SPLs and their subtypes. Study Type: Prospective. Population: Ninety‐five patients, 78 with malignant SPLs (including 48 with adenocarcinoma [AC] and 17 with squamous cell carcinoma [SCC]), and 17 with benign SPLs. Field Strength/Sequence: Fast spin‐echo (FSE) T2WI, FSE APTw and echo‐planar imaging IVIM, MR‐base attenuation correction (MRAC), and PET imaging on a 3‐T whole‐body PET/MR system. Assessment: The magnetization transfer ratio asymmetry (MTRasym) at 3.5 ppm, diffusion coefficient ( D ), pseudo diffusion coefficient ( D *), perfusion fraction ( f ), and the maximum standardized uptake value (SUVmax) were analyzed. Statistical Tests: Individual sample t ‐test, Delong test, Pearson's correlation analysis, and area under the receiver operating characteristic curve (AUC). P < 0.05 indicated statistical significance. Results: The MTRasym and SUVmax were significantly higher, and D was significantly lower in the malignant group (3.3 ± 2.6 [%], 7.8 ± 5, and 1.2 ± 0.3 [×10 −3 mm 2 /second]) compared to the benign group (−0.3 ± 1.6 [%], 3.1 ± 3.8, and 1.6 ± 0.3 [×10 −3 mm 2 /second]). The MTRasym and D were significantly lower, and SUVmax was significantly higher in the SCC group (0.8 ± 1.0 [%], 1.0 ± 0.2 [×10 −3 mm 2 /second] than in the AC group (4.1 ± 2.6 [%], 1.3 ± 0.3 [×10 −3 mm 2 /second], 6.7 ± 4.6). Besides, the combination (AUC = 0.964) of these three methods showed higher diagnostic efficacy than any individual method (AUC = 0.917, 0.851, 0.82, respectively) in identifying malignant and benign SPLs. However, APTw showed better diagnostic efficacy than the combination of three methods or PET imaging alone in distinguishing SCC and AC groups (AUC = 0.934, 0.781, 0.725, respectively). Data Conclusion: APTw, IVIM, and PET imaging are all effective methods to distinguish benign and malignant SPLs and their subtypes. APTw is potentially more capable than PET imaging of distinguishing lung SCC from AC. Level of Evidence: 2 Technical Efficacy: Stage 2